Praktik Akuntabilitas dalam Perspektif Tri Hita Kirana: Studi Etnografi di Pura Pitamaha Palangkaraya - Angelia , Novita Mayasari; Wibowo, Agus Satrya; Sudharma, Nyoman; Dawiyah, Baitul (PT. Sharia Journal and Education Center, 2024)
ABSTRACT This study aims to explore the practice of financial reporting accountability in Pura Pitamaha, Palangka Raya City based on the tri hita karana perspective. The ethnographic approach with triangulation techniques is used to explore the accounting in social interactions. The results show that vertical accountability and horizontal accountability have been carried out in the practice of financial reporting accountability. This is evident from the existence of financial reporting which states accountability in accordance with generally accepted accounting standards. However, the presentation of financial statements is still not in accordance with PSAK Number 45. Furthermore, based on the tri hita karana, accountability can be interpreted as vertical accountability, namely the relationship between humans and God (parahyangan). Meanwhile, horizontal accountability is defined as the relationship between humans and humans (pawongan) and the relationship between humans and the environment (palemahan). Keywords: Accountability, Ethnography, Tri Hita Karana ABSTRAK Studi ini bertujuan untuk mengeksplorasi praktik akuntabilitas laporan keuangan di Pura Pitamaha Palangka Raya berdasarkan perspektif tri hita karana. Pendekatan etnografi dengan tehnik triangulasi digunakan untuk menggali kehidupan akuntansi di dalam interaksi sosial kemasyarakatan. Hasil menunjukkan bahwa akuntabilitas vertikal dan akuntabilitas horisontal telah dijalankan dalam praktik akuntabilitas laporan keuangan. Hal ini tampak dengan adanya pelaporan keuangan yang menyatakan adanya pertanggungjawaban yang sesuai dengan standar akuntansi yang berlaku umum. Namun demikian, penyajian laporan keuangan masih belum sesuai dengan PSAK Nomor 45. Selanjutnya, berdasarkan tri hita karana bahwa akuntabilitas dapat dimaknai sebagai akuntabilitas vertikal yaitu hubungan manusia dengan Tuhan (parahyangan). Sedangkan akuntabilitas horisontal dimaknai dari hubungan manusia dengan manusia (pawongan) dan hubungan manusia dengan alam lingkungan (palemahan). Kata Kunci: Akuntabilitas, Etnografi, Tri Hita Karana